Feedback on research results to healthcare professionals in the context of HIV - Iací Proença Palmeira; Ivaneide Leal Ataíde Rodrigues; Elizabeth Teixeira; Bruna Alessandra Costa e Silva Panarra; Ana Isabella Sousa Almeida; Daiane Freitas Carneiro; Sâmela Stefane Corrêa Galvão
ABSTRACT Objective: Reporting the feedback on the results of a multicenter research for healthcare professionals that attend people living with HIV and AIDS in a Specialized Healthcare Center at Belém, state of Pará, Brazil. Method: Case report of the presentation and interpretation of research results, in 2015, totaling 25 participating professionals. The visual resource used was a data projector. Results: Participants reported the importance of the initiative, since, even though it is their right, feedback on research results is uncommon. Among the discussed issues, emerged the need for a culturally appropriate device for adequately strengthening educational practices carried out by healthcare professionals. Conclusion: Feedback on the research results enabled exchange of knowledge about the findings and production of new knowledge. In addition to achieving the social and ethical commitment of research, by promoting dissemination of results, enabling reflections on the reality in which they work.